KINERJA BADAN PERMUSYAWARATAN DESA DALAM PELAKSANAAN FUNGSI LEGISLASI DI KECAMATAN TALATAKO KABUPATEN TOJO UNA-UNA - Djabar, Kalsum M. ABD. (Katalogis, 2018)
This study aims to gain a deep understanding of the facts and answers to issues relating to performance Permusyawaratn Agency Village in Implementing Legislation Functions in Sub Talatako Tojo Una - Una. The results showed that of the five indicators to measure performance In the Village Consultative Body Function Implementation Legislation in District Talatako using Agus Dwiyanto theory that productivity, service quality, responsiveness, responsibility, and accountability. The performance of the five indicators, three indicators of productivity, quality of service and responsiveness not working well or still worse. While responsibility and accountability is already well underway. It can be concluded that the performance in the Village Consultative Body Function Implementation Legislation in District Talatako Tojo Una-Una is still not good.